Präklinische Fibrinolyse bei Patienten mit ST-Hebungsinfarkt in einer ländlich geprägten Region = Preclinical fibrinolysis in patients with ST-segment elevation myocardial infarction in a rural region - Viergutz, Tim; Grüttner, Joachim; Walter, Thomas; Weiß, Christel; Madler, Christian; Luiz, Thomas (Der Anaesthesist, 2016)
Background: In the current guidelines for the treatment of patients with ST-segment elevation myocardial infarction (STEMI), the European Society of Cardiology (ESC) recommends preclinical fibrinolysis as a reperfusion therapy if, due to long transportation times, no cardiac catheterisation is available within 90-120 min. However, there is little remaining in-depth expertise in this method because fibrinolysis is presently only rarely indicated. Methods: In a rural area in southwestern Germany, where an emergency primary percutaneous coronary intervention was not routinely available within 90-120 min, 156 STEMI patients underwent fibrinolysis with the plasminogen activator reteplase, performed by trained emergency physicians. The practicality of the treatment, as well as complications and the mortality of the patients in the preclinical phase until arrival at the hospital, were retrospectively studied. Results:The mean time from onset of the symptoms to first medical contact was 114 ± 116 min. The mean interval to the start of fibrinolysis of 13.5 ± 6.4 min was within the 30 min mandated by the ESC. Patients with inferior STEMI represented the largest subgroup. Occurring in 39 cases (25 %), complications due to infarction were relatively common during the prehospital phase, including 15 cases (9.6 %) of cardiogenic shock, but in all cases the complications were manageable. No patient died before arrival at the hospital. As lysis-associated adverse effects, merely two uncomplicated mucosal haemorrhages and one case of mild allergic skin reactions were seen. Conclusion: In emergency situations with long transportation times to the nearest suitable cardiac catheterisation laboratory, preclinical fibrinolysis in STEMI still represents a workable method. Success of this strategy requires particularly strong training of the emergency physicians in ECG and lysis therapy, and co-operation with nearby cardiac centres.